Microbial Spectrum of Complete Denture Wearer in Old Age People of Chitwan - Chaulagain, Rajib; Thakur, Smriti Narayan; Khanal, Bibek; Sapkota, Srijana Mishra; Chaudhary, Navin Kumar (Journal of Nepal Health Research Council, 2023)
Background: Human oral cavity contains many microorganisms, the habitat of which may be changed by complete denture among edentulous people. The complete dentures favor aggregation of microorganism. The aim of this study was to identify the microorganisms present in the complete dentures of old age people of Chitwan and assess the sensitivity pattern of the microorganisms to the common antibiotics. Methods: A descriptive cross-sectional study was conducted at Chitwan Medical College, Chitwan, Nepal among 45 old age people who have been wearing dentures above one year. The duration of the study was from 18th Nov 2021 to 12th May 2022. Swab was taken from the polished and tissue surfaces of both maxillary and mandibular dentures in the Department of Prosthodontics while the laboratory-based experiments were conducted in the Department of Microbiology. Antibiotic sensitivity was also done. The data was analyzed using Statistical Package for Social Science (SPSS) version 16.0. Descriptive statistics were used. The data was presented in form of frequency, percentage, mean and standard deviation. Results: Streptococcus spp. was predominant microorganism followed by Coagulase-negative Staphylococci and Staphylococcus aureus. The highest sensitivity pattern was observed to Amikacin, Nalidixic acid and Ciprofloxacin while the most resistant antibiotics were Amoxicillin/clavulanic acid and Cefixime. Escherichia coli was sensitive to all the tested antibiotics. Conclusions: In this study, Streptococcus spp. followed by Coagulase-negative Staphylococci and Staphylococcus aureus were the most frequently identified microorganisms from the dentures of old age people. Amikacin, Nalidixic acid and Ciprofloxacin were highly sensitive among the people of old age. Keywords: Antibiotic sensitivity; complete denture; microorganisms